Evidence of bias in randomized clinical trials of hepatitis C interferon therapies. (October 2017) - Tinè, Fabio; Attanasio, Massimo; Muggeo, Vito M R; Crainiceanu, Ciprian M.
Introduction: Bias may occur in randomized clinical trials in favor of the new experimental treatment because of unblinded assessment of subjective endpoints or wish bias. Using results from published trials, we analyzed and compared the treatment effect of hepatitis C antiviral interferon therapies experimental or control. Methods: Meta-regression of trials enrolling naïve hepatitis C virus patients that underwent four therapies including interferon alone or plus ribavirin during past years. The outcome measure was the sustained response evaluated by transaminases and/or hepatitis C virus-RNA serum load. Data on the outcome across therapies were collected according to the assigned arm (experimental or control) and to other trial and patient-level characteristics. Results: The overall difference in efficacy between the same treatment labeled experimental or control had a mean of +11.9% (p < 0.0001). The unadjusted difference favored the experimental therapies of group IFN-1 (+6%) and group IFN-3 (+10%), while there was no difference for group IFN-2 because of success rates from large multinational trials. In a meta-regression model with trial-specific random effects including several trial and patient-level variables, treatment and arm type remained significant (p < 0.0001 and p = 0.0009 respectively) in addition to drug-schedule-related variables. Conclusion: Our study indicates the same treatment is more effective when labeled "experimental" compared to when labeled "control" in a setting of trials using an objective endpoint and even after adjusting for patient and study-level characteristics. We discuss several factors related to design and conduct of hepatitis C trials as potential explanations of the bias toward the experimental treatment.